Listening to Family Life After Serious Pediatric Injury: A Study of Four Cases. Issue 3 (10th September 2019) - Mangelsdorf, Shaminka N.; Conroy, Rowena; Mehl, Matthias R.; Norton, Peter J.; Alisic, Eva
Abstract : Following a serious child injury, the entire family can be affected. Gaining an understanding of family support, interactions, and stress levels can help clinicians tailor treatment. Presently, these factors are assessed mainly via self‐reports and structured observations. We aimed to explore the value of naturalistic observation of postinjury parent–child interactions, in order to highlight how clinicians might use these data in their practice. Our qualitative study involved an in‐depth analysis of four cases from the Ear for Recovery project, against the backdrop of the larger sample's characteristics. Children who had been hospitalized with a serious injury wore the Electronically Activated Recorder (EAR). Over a two‐day period postdischarge, the EAR recorded 30‐second audio "snippets" every 5 minutes. Families also completed self‐report measures on family functioning, child stress and social support, parent stress, optimism, and self‐efficacy. For each case, two coders independently used an ethnographic method, integrating self‐report measures, family and injury characteristics, audio recordings, and transcripts to mimic integration of information within clinical practice. The coders then reached consensus on the main themes for each case through discussion. Families showed substantial variation in their communication in terms of content, tone, and frequency, including moments of conflict, humor, and injury‐related conversations. We explored how these recorded interactions converged with and diverged from the self‐report data. The EAR provided an opportunity for rich descriptions of individual families' communication and activities, yielding potential clinical information that may be otherwise difficult or impractical to obtain. Abstract : Después de una lesión pediátrica grave, toda la familia puede quedar afectada. Llegar a comprender el apoyo, las interacciones y los niveles de estrés de la familia puede ayudar a los profesionales a personalizar el tratamiento. Actualmente, estos factores se evalúan principalmente mediante autoinformes y observaciones estructuradas. Nuestra finalidad fue analizar el valor de la observación naturalista de las interacciones entre padres e hijos después de una lesión pediátrica a fin de destacar cómo los profesionales podrían usar estos datos en su práctica. Nuestro estudio cualitativo implicó un análisis profundo de cuatro casos del proyecto Ear for Recovery en el marco de las características de la muestra más grande. Los niños que habían sido hospitalizados con una lesión grave usaron la grabadora activada electrónicamente ( Electronically Activated Recorder, EAR). Durante un periodo de dos días posteriores al alta, la EAR grabó fragmentos de audio de 30 segundos cada 5 minutos. Las familias también completaron medidas de autoinforme sobre funcionamiento familiar, estrés infantil y apoyo social, estrés de los padres, optimismo y autoeficacia. Para cada caso, dos codificadores usaron independientemente un método etnográfico, integrando medidas de autoinforme, características de la familia y la lesión, grabaciones de audio y transcripciones para imitar la integración de la información dentro de la práctica clínica. Los codificadores luego se pusieron de acuerdo sobre los temas principales de cada caso mediante una charla. Las familias demostraron una variación considerable en su comunicación en cuanto al contenido, al tono y a la frecuencia, incluidos los momentos de conflicto, de humor y las conversaciones relacionadas con la lesión. Analizamos cómo estas interacciones grabadas coincidieron y se diferenciaron de los datos autoinformados. La EAR brindó la oportunidad de obtener descripciones detalladas de la comunicación y las actividades de cada familia en particular, y facilitó posible información clínica que de lo contrario puede ser difícil o impráctico obtener. Abstract : 儿童遭受严重伤害之后其所在家庭可能受到影响。获得对家庭支持、家庭成员互动和压力程度的了解之后, 临床医师可以给予针对性的治疗。目前, 这些因素主要是通过自我报告和系统观察的形式得以评估。我们试图探索伤害发生后, 针对家长与孩子之间在自然状态下的互动进行观察有何价值, 旨在强调这种自然观察的辅助作用, 因其帮助医师在实践中使用这些观察所得的数据。本文所作的质的研究包括对4个案例的深度分析, 他们选自于有较大样本的名为Ear for Recovery "倾听康复过程"的大型研究项目。因严重伤害而入住医院的那些儿童配戴电子激活记录仪(EAR), 离院后两天的时间内记录仪每五分钟记录30秒的小语音片段。参与的家庭完成各种量表的自评, 涉及方面有家庭功能, 儿童压力和社会支持, 家长压力, 乐观和自我效能感等。每个案例都配有两名数据分析人员, 他们分别独立地使用民族志研究方法, 结合自评量表的结果, 家庭和孩童所受伤害特点, 语音录音和相应的文本等等来模仿在临床实践中综合运用上述各类信息。两名研究者在对每一个案例讨论之后确定达成一致的主要主题。结果表明每个家庭的交流在内容, 语调, 交流频率方面都有非常大的差异, 具体包括冲突的时刻, 幽默, 和伤痛相关的话题等。我们探究了这些记录下来的互动与自我报告的数据之间相吻合和不一致的地方。EAR记录仪提供了非常好的机会来记录单个家庭的诸多交流和活动, 能借此产生大量病情相关信息, 而这些信息是不使用EAR时很难或无法在现实中获取的。